Integrating Tajribi, Experiential Learning, and Ngaji Rasa into Islamic Religious Education - Yahya Rafi Sya'bani; Abu Warasy Batula; Antiti Armilah; Nurlaila Turohmah; Robiatul Adawiyah Ramadhani; Zakaria Zakaria (PT. Student Rihlah Indonesia, 2026)
This study aims to develop a spiritual experience-based Islamic Religious Education (PAI) learning model by integrating the Tajribi method, David Kolb’s Experiential Learning theory, and the practice of Ngaji Rasa. The primary problem addressed is the current dominance of cognitive-informative approaches in PAI instruction, which frequently neglects the affective-spiritual dimension the core essence of Islamic education. Unlike previous research, this study synthesizes lived experience, inner reflection, Qur’anic meaning-making, and riyadhah (spiritual discipline) practices into a novel pedagogical framework. Employing a conceptual Research and Development (R&D) design, this study utilizes a theoretical synthesis approach to formulate an integrative instructional model. The findings reveal an epistemological and pedagogical convergence among the three approaches, manifested in a four-stage learning cycle: Tajribi Experience, Rasa Reflection, Qur'anic Conceptualization, and Riyadhah Action. The resulting Islamic Experiential Learning model offers a holistic framework that seamlessly blends concrete experience, inner reflection, Qur'an-based conceptualization, and continuous spiritual practice. Theoretically, this study contributes significantly to the advancement of the